Erasıng memory by transfer of property: the state, publıc enterprıses and cıvıl socıety ın the dıstrıbutıon of the abandoned propertıes durıng the early republıcan era - Eldem,Ali Emre (My University, 2017)
Tezin amacı, gayrimüslim azınlıklar tarafından bırakılan Emval-i Metruke’nin Erken Cumhuriyet Dönemi’nde dağıtım süreçlerini, dağıtım sürecinin aktörlerini ve Emval-i Metruke’den pay alan kamu kurumları ile sivil toplum örgütlerini incelemektir. Bu amaçla, T.C. Başbakanlık Cumhuriyet Arşivleri’nden alınan belgeler ve Türkiye'de yayınlanan yerel gazeteler birincil kaynaklar olarak kullanılmaktadır.

The aim of the thesis is to examine the distribution process of the abandoned properties left by the non-Muslim minorities, the actors of the distribution process and the public institutions and non-governmental organizations who took a share from abandoned properties during the Early Republican Era. For this purpose, documents from Prime Ministry Republican Archives and local newspapers published in Turkey are used as primary sources.
Keywords: 20. yy; Abandoned properties; Azınlıklar; Belgeler; civil society; collective memory; Early Republican Era; Emval-i Metruke; Erken Cumhuriyet Dönemi; gayrimüslim azınlıklar; Göç ve göçmenlik; İskan politikaları; Mübadele; non-Muslim minorities; sivil toplum; Siyaset ve yönetim; Tarih; Terkedilmiş mallar; toplumsal hafıza; transfer and distribution; transfer ve dağıtım; Türkiye; Uluslararası ilişkiler